2016
DOI: 10.1073/pnas.1607571113
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic features of chronic fatigue syndrome

Abstract: More than 2 million people in the United States have myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). We performed targeted, broad-spectrum metabolomics to gain insights into the biology of CFS. We studied a total of 84 subjects using these methods. Forty-five subjects (n = 22 men and 23 women) met diagnostic criteria for ME/CFS by Institute of Medicine, Canadian, and Fukuda criteria. Thirty-nine subjects (n = 18 men and 21 women) were age- and sex-matched normal controls. Males with CFS were 53 (±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
351
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 316 publications
(392 citation statements)
references
References 78 publications
34
351
0
7
Order By: Relevance
“…These findings were consistent with a lower ATP and GTP turnover and with decreased amounts of branched amino acid metabolic intermediates. However, there were also indications of reduced mitochondrial fatty acid oxidation only in female ME/CFS patients (32). Adding to PDH inhibition, reduced mitochondrial fatty acid oxidation would expectedly compromise the supply of acetyl-CoA further and thereby increase the dependency of category II amino acids for alternative fueling of the TCA cycle, as shown in our study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…These findings were consistent with a lower ATP and GTP turnover and with decreased amounts of branched amino acid metabolic intermediates. However, there were also indications of reduced mitochondrial fatty acid oxidation only in female ME/CFS patients (32). Adding to PDH inhibition, reduced mitochondrial fatty acid oxidation would expectedly compromise the supply of acetyl-CoA further and thereby increase the dependency of category II amino acids for alternative fueling of the TCA cycle, as shown in our study.…”
Section: Discussionsupporting
confidence: 57%
“…A recent study assessed 612 metabolites in 45 ME/CFS patients and 39 healthy controls and reported multiple abnormalities in several pathways involved in lipid metabolism and mitochondrial energy metabolism (32). The most prominent changes in ME/CFS patients were widespread decreases in sphingolipids, glycosphingolipids, and phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted, broad‐spectrum, plasma metabolomic analysis, covering 63 biochemical pathways, was performed by LC‐MS/MS as described previously44 with minor modifications. In all, 431 of 610 targeted metabolites were measureable in plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Recent metabolomics studies have found deficits in the pathways that generate energy from simple sugars, fatty acids, and amino acids (6)(7)(8)(9). Indeed, one study of over 600 metabolites, published in PNAS, found that the levels of most were unusually low, as occurs in states of hibernation (6).…”
Section: Studies Of Energy Metabolism Oxidative and Nitrosative Stressmentioning
confidence: 99%